A Software Agent Based Searching Approach for Constructivist Learning Over the Internet - Pan, Weidong; Huang, Mao Lin; Hawryszkiewycz, Igor (INFOCOMP Journal of Computer Science, 2004)
Finding out appropriate learning resources on the Internet is an important step in learning over Internet by using a constructivist method. Because the information available on the Internet grows rapidly, it is often difficult for a learner to search for a particular learning resource through navigating the large information sea. The use of commercial search engines can make the search much easier, but it is still difficult for the ordinary learners. This paper proposes the use of software agents to assist learners to find out required learning resources over the Internet. We present three approaches that the agent for an individual learner may use: 1) improve and optimize the search conducted by a commercial search engine, 2) seek advices from the teacher agents for appropriate learning resources and 3) seek suggestions for appropriate learning resources from the fellow student agents. Based on the analysis of the advantages and disadvantages of these approaches, a combined implementation is further proposed. Finally we describe the preliminary results and the outlooks of the research.